Hierarchy of RG flows in 6d (1, 0) orbi-instantons - Marco Fazzi; Suvendu Giri (Journal of High Energy Physics, 2022)
Abstract N M5-branes probing the intersection between the orbifold ℂ2 /ΓADE and an E 8 wall give rise to 6d (1, 0) SCFTs known as ADE-type orbi-instantons. At fixed N and order of the orbifold, each element of Hom(ΓADE , E 8) defines a different SCFT. The SCFTs are connected by Higgs branch RG flows, which generically reduce the flavor symmetry of the UV fixed point. We determine the full hierarchy of these RG flows for type A, i.e. ℂ2 /ℤ k , for any value of N and k. The hierarchy takes the form of an intricate Hasse diagram: each node represents an IR orbi-instanton (homomorphism), and each edge an allowed flow, compatibly with the 6d a-theorem. The partial order is defined via quiver subtraction of the 3d magnetic quivers associated with the 6d SCFTs, which is equivalent to performing a so-called Kraft-Procesi transition between homomorphisms.